Food Safety Knowledge, Hygiene Practices, and Food Preparation and Storage Behaviors among Domestic Food Handlers - Malja Afzal; Zoha Sohail; Mnahil Moazzam; Zaniab Akram (International Health Review, 2025)
Food safety is an important component of public health. The World Health Organization (WHO) states that access to safe and nutritious food is essential for the overall health and well-being of an individual. Over 200 diseases, ranging from diarrhea to cancer, are caused by the consumption of food contaminated with harmful bacteria, viruses, parasites, and chemical substances. Unsafe practices within household and commercial food environments can contribute to foodborne illness. The current study focused on assessing the knowledge of food safety, hygiene preparation, and storage practices among domestic food handlers. A cross-sectional study was conducted with 116 adults aged 19-65 years. A convenient sampling technique was used to collect the sample from Lahore, Pakistan. Data was collected using a structured questionnaire that covered five domains of food safety: (I) demographic profile, (II) food safety knowledge, (III) personal hygiene practices, (IV) food purchasing practices, and (V) food preparation and storage practices. Data analysis was carried out using the IBM SPSS software version 25. Most of the participants demonstrated basic knowledge of foodborne illnesses and the importance of hand hygiene. However, a lack of awareness was identified regarding refrigeration, storage temperatures, and checking food labels and expiration dates. Cross-contamination was observed as many respondents use the same cutting boards and utensils for raw and cooked foods. There was also a lack of understanding regarding the ideal meat storage and temperatures. Domestic food handlers possessed knowledge about foodborne illnesses, yet there are gaps in storage practices, contamination prevention, and label checking. Improving food safety education and emphasizing personal hygiene can effectively mitigate the risk of foodborne illnesses.